Emerging Roles of Neuronal Ca2+ Sensor-1 in Cardiac and Neuronal Tissues: A Mini Review - Nakamura, Tomoe Y.; Nakao, Shu; Wakabayashi, Shigeo (Frontiers in Molecular Neuroscience, 2019)
The EF-hand Ca2+-binding protein, Neuronal Ca2+ Sensor-1 (NCS-1/frequenin), is predominantly expressed in neuronal tissues and plays a crucial role in neuronal functions, including synaptic transmission and plasticity. NCS-1 has diverse functional roles, as elucidated in the past 15 years, which include the regulation of phosphatidylinositol 4-kinase IIIβ and several ion channels such as voltage-gated K+ and Ca2+ channels, the D2 dopamine receptor, and inositol 1,4,5-trisphosphate receptors (InsP3Rs). Functional analyses demonstrated that NCS-1 enhances exocytosis and neuronal survival after injury, as well as promotes learning and memory in mice. NCS-1 is also expressed in the heart including the Purkinje fibers (PFs) of the conduction system. NCS-1 interacts with Kv4 K+ channels together with dipeptidyl peptidase-like protein-6, and this macromolecule then composes the transient outward current (Ito) in PFs and contributes to the repolarization of PF action potential, thus being responsible for idiopathic arrhythmia. Moreover, NCS-1 expression was reported to be significantly high at the immature stage and at hypertrophy in adults. That report demonstrated that NCS-1 positively regulates cardiac contraction in immature hearts by increasing intracellular Ca2+ signals through interaction with InsP3Rs. With the related signals, NCS-1 activates nuclear Ca2+ signals, which would be a mechanism underlying hormone-induced cardiac hypertrophy. Furthermore, NCS-1 contributes to stress tolerance in cardiomyocytes by activating mitochondrial detoxification pathways, with a key role in Ca2+-dependent pathways. In this review, we will discuss recent findings supporting the functional significance of NCS-1 in the brain and heart and will address possible underlying molecular mechanisms.